The in vivo digestibility and creatinine excretion pattern of lambs fed plantain (Plantago lanceolata L.) and perennial ryegrass (Lolium perenne L.) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Palmerston North, New Zealand - Fletcher, Hannah (Massey University, 2025)
The loss of nitrogen from sheep-grazed pastures can have negative effects on the environment via leaching of nitrate and nitrous oxide emissions. To be able to accurately measure or estimate nitrate leaching and nitrous oxide emissions it is important to be able to quantify urine output from livestock, however this is difficult to do with grazing sheep. This research was carried out with two main research objectives. The first was to investigate the creatinine excretion pattern of sheep fed perennial ryegrass (Lolium perenne L.) or plantain (Plantago lanceolata L.) at different times of the day. Creatinine is a nitrogenous compound only excreted in urine. It has been used to predict urine volume, accurately with cattle but there is a large amount of unexplained variation when using this method with sheep. The time of day has been proposed as a potential factor of creatinine concentration which may affect the accuracy of predictions. The second objective was to measure the in vivo digestibility of these two forages with sheep. Digestibility of the two forages (especially plantain) has not been studied extensively in vivo in New Zealand for sheep and older digestibility data may not be relevant to modern sheep. It was hypothesised that plantain will have a lower DM digestibility in vivo. An 8-day indoor metabolism trial (3-day adaptation period and 5-day collection phase) was conducted using eleven castrated Romney-cross wether lambs. The lambs used were split into two groups (Plantain (n=5) and Ryegrass (n=6)) that were balanced by liveweight. Urine samples were taken from the lambs at 6am, 9am, 12pm, 3pm and 6pm (4 x 3-hour intervals and 1 x 12-hour interval) over 4 days and analysed for concentration of creatinine. Further, the total collection method was applied and feed, feed refusals, faeces and urine were all weighed and sampled to determine in vivo digestibility. Forage treatment had no influence on the amount of creatinine excreted by sheep or the digestibility of dry matter, ash, fat, nitrogen, neutral detergent fibre, acid detergent fibre and gross energy (p>0.05) but did affect creatinine concentration and lignin digestibility (p 43.8%, p<0.05). The measured lignin digestibility was high for both forages and greater for the plantain than the perennial ryegrass (76.7% > 43.8%, p<0.05). This suggests lignin may not be a good indicator of DM or NDF digestibility. The time of day affected both creatinine concentration and the amount of creatine excreted per hour (p.<0.05). Therefore, to improve the accuracy of urine volume predictions identifying a time when creatinine concentration in the urine of sheep is consistently representative of the mean daily creatinine concentration may be beneficial. The results of this experiment suggest this period might be in the early afternoon during the 12pm-3pm period (approximately 6 hours after the lambs were given fresh feed) as this period had the closest mean creatinine concentrations to the daily mean.
Keywords: 300307 Environmental studies in animal production